Differential expression of c-kit and CD43 in histological subtypes of adenoid cystic carcinoma of salivary gland - Mohamed M. Ahmed; Eman A. Abo-Hager (Saudi Dental Journal)
Adenoid cystic carcinoma (ACC) of the salivary gland is characterized by a prolonged but inevitably unfavorable clinical course. Recent studies have suggested that the transmembrane tyrosine kinase receptor, c-kit proto-oncogene is involved in ACC pathogenesis. CD43 is a sialoglycoprotein that is typically expressed by hematopoietic cells and their derivative neoplasms, although positivity in epithelial tumors has only been recognized recently. Objective: The aim of this study was to evaluate c-kit and CD43 immunoreactivity in ACCs and to compare the extent of their expression in various histologically defined subgroups of ACC, and their probable involvement in ACC pathogenesis. Study design: Formalin-fixed paraffin-embedded sections from 35 ACCs were immunostained for c-kit and CD43 using monoclonal antibodies. Results: Cytoplasmic and membranous c-kit immunoreactivity was detected in 25/35 ACCs (71.4%) with strong immunostaining observed in solid pattern of ACC. Cytoplasmic and membranous CD43 immunoreactivity was detected in 18/35 (51.4%) of ACCs with strong immunostaining seen in the cribriform pattern. Conclusions: These results suggested that c-kit could be used as a prognostic marker for ACC and specific c-kit tyrosine kinase inhibitors such as imatinib, might be used in future therapeutic approaches against subgroups of ACC. CD43 appears to be preferentially expressed in salivary gland ACCs. Its expression decreased with cellular dedifferentiation and there was an inverse relationship between immunoexpression of c-kit and CD43 among ACC of salivary gland. Keywords: Adenoid cystic carcinoma (ACC), Salivary gland, Immunohistochemistry, c-kit, CD43